Hubungan Pengetahuan Gizi Ibu Dan Status Imunisasi DasarBalita Dengan Status Gizi Balita Di Daerah PolokartoWilayah Kerja Puskesmas Polokarto Sukoharjo - WIJAYA, MAULANA, Dwi Sarbini, SST, M.Kes, Luluk Ria Rakhma, S.Gz., M.Gizi (2016)
Background: One of the factors that influence nutritional status nutritional knowledge. In addition to knowledge, immune system also have an influence on nutritional status. Immunisation is a way to enhance the person's immune system is actively against a disease, so avoid the disease. Objective: To know the relationship of knowledge of nutrition and immunization status of mothers with basic nutritional status toddler in the area Polokarto Work area Clinics Polokarto Sukoharjo. Methods: the study was descriptive in nature design correlation with cross sectional. The mother's nutrition know ledge data using direct interview using Questionnaires sheet and immunization data base look at KIA to the number of complete immunization 12 times while the nutritional status of toddlers with measurements BB/U. Of data analysis used is correlation Spearman Rank and Fisher's Exact Test. Results: Knowledge of good maternal nutrition (65.3%) and less maternal nutrition knowledge (34.7%), basic immunization status unknown status are fully immunized (85.7%) and basic immunization status is incomplete (14.3% ), nutritional status of children under five are known with good nutritional status (74.5%), malnutrition status (16.3%), poor nutritional status (7.1%) and a better nutritional status (2.1%). The test results relations maternal nutrition knowledge and nutritional status with p value 0.385. Hail test of basic immunization status relationship with the nutritional status of children with p value 0.509. Conclusion: There is no maternal nutrition knowledge relationship with the nutritional status of children and there is no basic immunization status relationship with the nutritional status of children.